Diversity and use of plant and animal species in backyards of Nunkiní, Campeche, Mexico - Magaña Magaña, Miguel Angel (2026)
Introduction. In rural areas, backyard agricultural production satisfies part of the food needs of families, provides health benefits, and contributes to the conservation of the biological diversity of plants and animals. Objective. To quantify, using ecological indices, the diversity of plant and animal species present in the backyards of Nunkiní, Campeche, Mexico, and to analyze their main forms of use. Materials and methods. The information was obtained through a survey with directed sampling applied to the female heads of household units in the community of Nunkiní, Campeche, Mexico. Fieldwork was conducted between August and November 2023, during which 33 household units were visited. The survey included sections on family composition, backyard characteristics, an inventory of plants and animals, and the forms of use of both. The Shannon and Margalef indices were estimated to determine diversity and relative abundance. Results. The presence of 179 plant species and 20 animal species was recorded. Diversity and abundance were high for plant species (H’ = 4.243; Margalef = 23.3), whereas for animal species they were low (H’ = 1.204) or medium (Margalef = 2.60). Eight uses were identified for plant species and ten for animal species. Conclusions. In the sampled backyards, most of the diversity is composed of plant species, with predominance of those belonging to the Cactaceae family. Animal diversity represents 11.2 % of the total recorded species, most of which belong to the Phasianidae family. The main forms of use of the plant component were ornamental and food, whereas in the animal component their contribution to food and the generation of economic income stood out.